Case Study On Tenarium Sdn. Bhd. - Lee, Richard Yoong Hwa (2004)
Tenarium Sdn Bhd is a provider of a new class of software, called EMT - Efficiency Management and Tracking - that allows managers to oversee their day-to day operations from a single point of control.The main benefit of applying the EMT concept at manufacturing facilities is that it allows managers to think naturally about their operations, instead of translating to and from financial data.